Studi Penilaian Kinerja Irigasi dan Angka Kebutuhan Nyata Operasi dan Pemeliharaan (AKNOP) pada Daerah Irigasi Sumber Mujur Kecamatan Candipuro Kabupaten Lumajang - Rizaldy, Muhammad Fahmi; Prayogo, Tri Budi; Wahyuni, Sri (Fakultas Teknik, Universitas Brawijaya, 2021)
The Sumber Mujur Irrigation Area is located in Candipuro District with the broncaptering as the main building which is located in Sumber Mujur Subdistrict. In fact, in this Irrigation Area, there are many damages and problems to the assets owned. From the results of the inventory carried out, there were 109 problem points. Damage and problems are found at six points in the main building, 30 points on the carrier channel, and 73 points on the building on the carrier channel. The performance index value of Sumber Mujur Irrigation Area got a score of 81.94% which consists of physical infrastructure is 33.9%, plant productivity is 14.5%, operation and management supporting facilities is 8.5%, personnel organization is 11.7%, documentation 4.18%, water user farmer association is 9.15%. The calculation of priority for rehabilitation in the Sumber Mujur Irrigation Area using the AHP and ANP method, the aspect that requires rehabilitation most is the Physical Infrastructure aspect of the Main Building aspect. For Real Cost Value of Maintaining and Operating Irrigation calculation (AKNOP) for the main building in the Sumber Mujur Irrigation Area, it was obtained IDR 574,871,655.00.